The Law on Modifying the Engine of a Two-Wheel Motor Vehicle Perspective of Sadd Adz-Dzari’ah - Lubis, Pangeran Fatih Hasyim; Lubis, Fauziah (Universitas Muhammadiyah Ponorogo, 2025)
This study discusses the practice of engine modification on motorcycles in the Medan Tembung District, specifically at the MRT Garage workshop. The modifications are carried out at the request of customers to increase engine capacity. However, this practice is often considered illegal because it does not comply with safety standards and existing regulations in Indonesia. This study analyzes the phenomenon from the perspective of Sadd Adz-Dzari’ah in Islamic law, which prohibits actions that have the potential to lead to harm, even if initially permitted. The study also examines Indonesian legal regulations such as Government Regulation No. 55 of 2012 and Law No. 22 of 2009, which regulate the technical aspects of motor vehicle modifications. The findings show that such modification practices violate both Islamic law and government regulations, as they cause harm such as vehicle instability and an increased risk of accidents. This study contributes to the understanding of motor vehicle modification regulations from both Islamic and Indonesian positive law perspectives.